Species-Specific Differences in the Microbiomes and Organic Exudates of Crustose Coralline Algae Influence Bacterioplankton Communities - Quinlan, Zachary A.; Ritson-Williams, Raphael; Carroll, Brenna J.; Carlson, Craig A.; Nelson, Craig E. (Frontiers in Microbiology, 2019)
Crustose coralline algae (CCA) have been shown to play a significant role in the settlement of coral larvae through either the production of chemical or the facilitation of specific microbial communities. However, recently it has been shown that some species of CCA inhibit this settlement. Moreover, it is largely unknown how the dissolved organic matter (DOM) exudates differ between CCA species and what bacterioplankton communities these exudates facilitate. We conducted single-day exudation experiments on two species of CCA, one which facilitates and one which inhibits coral larval settlement to contrast DOM production and this drives the microbial communities of both the tissue microbiome and bacterioplankton. We collected exudates from Hydrolithon reinboldii and Porolithon onkodes in both filter-sterilized seawater and unfiltered seawater. Our results demonstrate that both species produce equivalent quantities of dissolved organic carbon which differ in composition and facilitate distinct microbial communities. P. onkodes exudates facilitate more OTUs which are more correlated with coral disease, whereas H. reinboldii facilitated OTUs which have been shown to produce antimicrobial compounds. Our results begin to parse the differences in DOM exudation between CCA species and their potential to influence coral larval settlement.